The Implementation of Village Digitalization Through Application OpenSID for Quality and Quality Improvement Public Service - Taufik, Abd. Rohman (Jurnal Akuntansi AKUNESA, 2025)
This study aims to evaluate the implementation of village digitization using the OpenSID system as an effort to improve the quality and quality of public services in Tambakrejo Village. The method used is qualitative research with a case study approach. Research data were collected through observation, interviews, and analysis of related documents. The data was analyzed using qualitative analysis techniques to gain a deep understanding of the implementation of village digitization through OpenSID . The results of the study show that the implementation of village digitization through OpenSID in Tambakrejo Village has had a positive impact on improving the quality and quality of public services. Digitizing population administration through OpenSID has facilitated the accessibility of population data, reduced administrative errors, and accelerated the process of population administration services such as population registration, updating data, and issuing population documents. In addition, the implementation of OpenSID administration has also increased transparency and accountability in population governance. However, this study also identified several challenges faced in implementing village digitization through OpenSID .